Estimations of overdiagnosis in breast cancer screening vary between 0% and over 50%: why? - Catherine Hill; Dan Chaltiel (BMJ Open)
Background Published estimations of the extent of breast cancer overdiagnosis vary widely, and there have been heated debates around these estimations. Some high estimates have even been the basis of campaigns against national breast cancer screening programmes. Identifying some of the sources of heterogeneity between different estimates would help to clarify the issue.Methods The simple case of neuroblastoma—a childhood cancer—screening is used to describe the basic principle of overdiagnosis estimation. The more complicated mechanism of breast cancer overdiagnosis is described based on data from Denmark, taking into account the type of data used, individual or aggregated.Findings The type of data used in overdiagnosis studies has a meaningful effect on the estimation: no study based on individual data provides an estimate higher than 17%, while studies based on aggregated data often provide estimates higher than 40%. This is too systematic to be random. The analysis of two Danish studies, one of each kind, highlights the biases that come with the use of aggregated data and shows how they can lead to overdiagnosis.Interpretation Many estimates of overdiagnosis associated with breast cancer screening programmes are serious overestimations.